Fueling the debate: robust quantification of cartel impact on gas stations - Amat, Bruno Motta (2024)
This work examines the heterogeneity in cartel overcharges within the Brazilian fuel retail market. The study involves constructing a unique dataset that combines firm-level microdata on profit margins with legal details about each cartel case. Employing a differences-in-differences approach, my findings reveal variability in overcharges across different cases. I analyze how various factors, such as market characteristics and the internal organization of cartels, contribute to this variability. I observe that the participation of other members, such as the gas station union and wholesalers, impacts the overcharges. While the involvement of the gas station union tends to increase overcharges, the participation of wholesalers generally decreases the overcharge for retailers.